Implementing Task-Based Instruction to Facilitate Language Learning: Moving Away from Theory - Aileen Griffiths (TEFLIN Journal, 2015)
The use of tasks has gained growing acceptance in the field of language teaching. In the task-based teaching, the organization of the language lassroom is learner-centered and the learning activities involve communicative language use. This paper discusses task-based teaching by presenting a brief overview of its underlying rationales. The rationales for infcoporating taskbased activities are dirived from the psycholinguistic and pedagogical perpectives. Some practical in-sights in this paper might be useful for English teachers and language experts.